Complement genetics, deficiencies, and disease associations - Mayilyan, Karine R. (Protein Cell, 2012)
The complement system is a key component of innate immunity. More than 45 genes encoding the proteins of complement components or their isotypes and subunits, receptors, and regulators have been discovered. These genes are distributed throughout different chromosomes, with 19 genes comprising three significant complement gene clusters in the human genome. Genetic deficiency of any early component of the classical pathway (C1q, C1r/s, C2, C4, and C3) is associated with autoimmune diseases due to the failure of clearance of immune complexes (IC) and apoptotic materials, and the impairment of normal humoral response. Deficiencies of mannan-binding lectin (MBL) and the early components of the alternative (factor D, properdin) and terminal pathways (from C3 onward components: C5, C6, C7, C8, C9) increase susceptibility to infections and their recurrence. While the association of MBL deficiency with a number of autoimmune and infectious disorders has been well established, the effects of the deficiency of other lectin pathway components (ficolins, MASPs) have been less extensively investigated due to our incomplete knowledge of the genetic background of such deficiencies and the functional activity of those components. For complement regulators and receptors, the consequences of their genetic deficiency vary depending on their specific involvement in the regulatory or signalling steps within the complement cascade and beyond. This article reviews current knowledge and concepts about the genetic load of complement component deficiencies and their association with diseases. An integrative presentation of genetic data with the latest updates provides a background to further investigations of the disease association investigations of the complement system from the perspective of systems biology and systems genetics.